Digital skill proficiency and data analytical usage among public-sector internal auditors of the accountant general’s department of Malaysia: advancing audit digitalisation - Ismail, Suhaiza; Mokhtar, Norsyahida; Ahmad @ Abdul Mutalib, Hawa (Institut Perakaunan Negara, 2025)
Purpose: The current study aims to explore the level of digital skill proficiency among public-sector internal auditors of the Accountant General’s Department (AGD) of Malaysia and examine the degree of data analytical usage among the auditors. Design/ Methodology/ Approach: An online survey questionnaire was employed to gather data from a population of 124 public-sector internal auditors from the Internal Audit Management Division (BPAD) of the AGD Malaysia. Descriptive statistics, including mean scores, standard deviation, and mean score ranking, were utilised to determine the level of digital skill proficiency and data analytical usage. In addition, a focus group discussion was conducted with AGD officers to support the statistical findings. Findings: The results revealed that public-sector internal auditors averagely possessed moderate levels of digital skill proficiency, with limited data analytics types. Microsoft Excel was the most extensively employed software among the auditors. Originality: The empirical findings contributed novel insights into the current levels of digital skill proficiency and data analytical usage, which served as a valuable foundation for developing targeted strategies to advance the digital audit transformation agenda